(3eNJUQ aj Yde GdeaJhM GdghGFis - (3YeGO GdOjf CHi GdYHGS CMeO Hf eMeO GdeYQha HGHf GdgGFes; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi fYeGFg hGdTcQ dg Ydi CdGFg agPG eNJUQ hMjR ai Yde GdMSGH GdeaJhM GdghGFi s
(3HgG fgGjI cJGH (B" (3fUGH GdLHQ ai MSGH GdLHQ dGHf adhS(B"s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs